2015
DOI: 10.2147/ijn.s79528
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing apoptotic neurons in Alzheimer’s disease using wheat germ agglutinin-conjugated and cardiolipin-conjugated liposomes with encapsulated nerve growth factor and curcumin

Abstract: Liposomes with cardiolipin (CL) and wheat germ agglutinin (WGA) were developed to permeate the blood–brain barrier and treat Alzheimer’s disease. WGA-conjugated and CL-incorporated liposomes (WGA-CL-liposomes) were used to transport nerve growth factor (NGF) and curcumin (CUR) across a monolayer of human brain-microvascular endothelial cells regulated by human astrocytes and to protect SK-N-MC cells against apoptosis induced by β-amyloid 1–42 (Aβ 1–42 ) fibrils. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…As shown in Table 1, all these profiles showed very good linearity with fitting degree higher than 0.99 (regression equations are also displayed), suggesting that the release of Cur-LPs fitted to zero-order kinetics. In other similar studies, the release of curcumin from liposome was found to be non-linear [38,39]. From the point view of drug research and development, zero-order release kinetics is the most ideal release profile because it provides a constant drug release rate and thus is able to maintain therapeutic effect for a long time, decrease administration times, and reduce side effects.…”
Section: In Vitro Releasementioning
confidence: 91%
“…As shown in Table 1, all these profiles showed very good linearity with fitting degree higher than 0.99 (regression equations are also displayed), suggesting that the release of Cur-LPs fitted to zero-order kinetics. In other similar studies, the release of curcumin from liposome was found to be non-linear [38,39]. From the point view of drug research and development, zero-order release kinetics is the most ideal release profile because it provides a constant drug release rate and thus is able to maintain therapeutic effect for a long time, decrease administration times, and reduce side effects.…”
Section: In Vitro Releasementioning
confidence: 91%
“…WGA could binds to N-acetyl-D-glucosamine and sialic acid with low toxicity to the normal tissues [15]. It was reported that WGA could enhance the transport ability across the BBB by receptor-mediated endocytosis [16], and the modification of WGA on nanoparticles could potentiate the targeting effects to tumor cells by the specifically binding to glycoproteins overexpressed on cytomembrane [17]. As one of the most useful strategies, cationic liposomes have been used as excellent delivery carriers for their targeting property to tumor cells or tumor vascular cells by electrostatic interaction [18].…”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, exogenous NGF is regarded as an important bioactive element with inadequate bioavailability in the brain because it is hydrophilic and bulky with a molecular weight of 27 kDa. 30 The current LIP carriers with WGA and CL could be practical formulations to enhance the usability of CRM and NGF in the brain. As shown in Figure 1F, the order in the cytotoxicity was CRM ≅ WGA-CRM-CL/LIP .…”
mentioning
confidence: 99%